0019 The occupational JP8 exposure neuroepidemiology study; evaluation of neuropsychological effects. (23rd June 2014) - Proctor, Susan; Heaton, Kristin; Smith, Kristen; Rodrigues, Ema; McClean, Michael
Abstract : Objectives: One of the most prevalent workplace chemical exposures historically and currently confronting the global military and civilian workforce is jet propellant (JP) fuel. To date, numerous protective and preventive strategies have been put in place to minimise acutely toxic exposure levels. However, questions remain regarding the effect of repeated exposures at lower (than regulated) levels. The Occupational JP8 Exposure Neuroepidemiology Study was designed to examine the relationships between repeated-workday occupational JP8 exposure among Air Force (AF) personnel and specific aspects of central nervous system function, including neuropsychological task performances. Method: Seventy-four AF personnel consented to participate in the 6-day study and were administered two distinct neuropsychological task batteries (labelled 'Day 1' and multi-day 'Repeated Day'). JP8 exposure was measured by personal breathing zone total hydrocarbons, naphthalene, benzene, toluene, ethylbenzene, and xylene and urinary biomarkers (e.g., 1- and 2-naphthol). Multivariate linear regression analyses were conducted to examine relationships between current and historical levels of JP8 exposure and neuropsychological performances. Linear mixed effects analyses were conducted to examine relationships between workday JP8 exposure on neuropsychological functioning over a work week. Results: Reduced proficiency of tasks involving verbal memory and attention was demonstrated among those with higher versus lower, current JP8 exposure. Significant associations were not observed between repeated-workday exposure to JP8 and neuropsychological performances. Conclusions: Results suggest that repeated JP-8 exposure, at levels not exceeding regulatory limits, does not significantly contribute to reduced neuropsychological proficiencies. We discuss potential explanations and implications for these findings.